2006
DOI: 10.1128/jvi.01216-06
|View full text |Cite
|
Sign up to set email alerts
|

Herpes Simplex Virus ICP27 Is Required for Virus-Induced Stabilization of the ARE-Containing IEX-1 mRNA Encoded by the Human IER3 Gene

Abstract: Herpes simplex virus (HSV) stifles cellular gene expression during productive infection of permissive cells, thereby diminishing host responses to infection. Host shutoff is achieved largely through the complementary actions of two viral proteins, ICP27 and virion host shutoff (vhs), that inhibit cellular mRNA biogenesis and trigger global mRNA decay, respectively. Although most cellular mRNAs are thus depleted, some instead increase in abundance after infection; perhaps surprisingly, some of these contain AU-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
38
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 93 publications
1
38
0
Order By: Relevance
“…Previous reports using viral deletion mutants have shown that ICP27 expression is required during HSV-1 infection for p38 activation (12,23,24). The study presented in this paper, however, is the first to show that ICP27 expression alone is sufficient for the activation of p38 signaling.…”
Section: Discussionmentioning
confidence: 47%
See 3 more Smart Citations
“…Previous reports using viral deletion mutants have shown that ICP27 expression is required during HSV-1 infection for p38 activation (12,23,24). The study presented in this paper, however, is the first to show that ICP27 expression alone is sufficient for the activation of p38 signaling.…”
Section: Discussionmentioning
confidence: 47%
“…The timing of the activation pointed toward an IE gene product as being responsible for initial induction since IE proteins are present at high levels at 3 hpi. Consistent with this, studies showed that ICP27 is required in the context of viral infection for activation of the SAPK pathways (12,23,24). The N-terminal end of the ICP27 protein, which plays a functional role in nuclear export, is required for SAPK activation (12,23,33).…”
mentioning
confidence: 67%
See 2 more Smart Citations
“…Besides an induced gene transcription mediated by the p44/p42 MAPK and AP1 pathway, stabilization of IEX-1 mRNA by G17 may also account for the elevated IEX-1 expression. IEX-1 mRNA contains a half-life time-regulating A-rich element (ARE) within its 3 0 -UTR, and this element is under the control of the p38 MAPK pathway (Corcoran et al, 2006), which is induced in Colo320wt cells by G17 as well (Yu et al, 2005). Of note, G17 similarly induces IEX-1 expression in the colorectal cancer cell line LoVo (Supplementary material 2) also expressing the CCK-2 receptor and exhibiting an apoptotic response to G17 treatment .…”
Section: Discussionmentioning
confidence: 99%